Applications and Prospects of SLAM Technology in Mobile Robot Design - Chen, Baixu (Transactions on Computer Science and Intelligent Systems Research, 2024)
This paper studies the application of simultaneous localization and mapping (SLAM) technology in the design of mobile robots. Traditional SLAM research lacks a systematic approach and adaptability to actual work tasks, making it difficult for researchers to choose reasonable architectures for optimized design, thereby limiting the further development of SLAM technology. The paper begins by introducing the definition and development history of SLAM technology, then introduces six kinds of SLAM technologies in the application framework of mobile robots, comparing and analyzing their applicable scenes based on each technology’s characteristics. It proceeds to analyze typical applications of mobile robots with SLAM technology in Autonomous Mobile Robots and three-dimensional (3D) environment exploration, as well as search and rescue operations, rounding off with an analysis and summary of prospects of SLAM technology in mobile robot design. This study offers targeted solutions by employing listing and comparison methods combined with practical application analysis, thus better-assisting researchers in choosing reasonable architectures for optimization. This paper facilitates researchers in choosing reasonable architectures for designing mobile robots under different scenarios. In conclusion, it proposes prospects of SLAM technology in mobile robot design, providing direction for research on SLAM technology in mobile robots.